Scientific Approaches to Defining the Essence of Cross-border Market Tourist and Recreational Services (Economic journal of Lesya Ukrainka Volyn National University, 2016)
It was revealed, that the complex of scientific and practical problems are related to the definition of cross-border nature of the market of tourist and recreational services and remains under-researched in the foreign and domestic scientific literature. There is also reveals the social economic contentof tourist and recreational services, cross-border nature of the author's definition of the market of tourist and recreational services. It is very important and effective to use a systematic approach for exploration of cross-border market of tourist and recreational services.These principles will reveal the essence of cross-border market of tourist and recreational services as a major social and economic system with different parameters, what is the part of another system – the cross-border region economy. Defined subjects and objects of cross-border market tourist and recreational services as a complex socio-economic system.Subjects and objects of cross-border market of tourist and recreational services are described as a complex of socio-economic system.
Keywords: tourism, recreation, tourism and recreational services, cross-border market, cross-border market of tourist and recreational services